Is hyperprogressive disease a specific phenomenom of immunotherapy? - Marta Brambilla; Giuseppe Lo Russo; Roberto Ferrara; Sara Manglaviti; Marina Chiara Garassino; Mario Occhipinti (Open Exploration Publishing Inc., 2020)
Hyperprogressive disease (HPD) is a novel pattern of response during immunotherapy treatment. Several retrospective studies have evaluated its prevalence among various cancer types and, in particular, in non-small cell lung cancer patients, based on different definition criteria. If HPD is a just a typical phenomenon of immunotherapy is still an unsolved concern. This paper summarized the available data about HPD in other cancer treatments.